Catalytic oxidation of primary and secondary alcohols over a novel TCPP/Zn–Fe2O4@ZnO catalyst. Issue 121 (20th November 2015) - Heidari-Golafzani, Mahdi; Rabbani, Mahboubeh; Rahimi, Rahmatollah; Azad, Alireza
Abstract : The catalytic activity of TCPP/Zn–Fe2 O4 @ZnO as a recyclable and high efficiency heterogeneous catalyst for oxidation of primary and secondary alcohols using H2 O2 as a green oxidant under reflux conditions in CH3 CN was investigated. Abstract : The catalytic activity of TCPP/Zn–Fe2 O4 @ZnO as a recyclable and high efficiency heterogeneous catalyst for oxidation of primary and secondary alcohols using aqueous hydrogen peroxide as a green oxidant under reflux conditions in CH3 CN was investigated. The catalyst could be magnetically recovered and reused for future runs without significant decrease in its activity and selectivity. The excellent selectivity (100%) was achieved under reaction conditions. Furthermore, X-ray diffraction (XRD), diffuse reflectance spectroscopy (DRS), Fourier transform infrared (FT-IR), vibrating sample magnetometry (VSM), transition electron microscopy (TEM), scanning electron microscopy (SEM), X-ray fluorescence analysis (XRF) and energy dispersive X-ray analysis (EDX) were used for the catalyst characterization.